Psidium Exotic and Native Species from Brazil Abolish Depression-like Behavior and Oxidative Stress induced by Corticosterone in Mice - Zeni, Ana Lúcia Bertarello; Dalmagro, Ana Paula; Junges, Lucas Henrique; Cavichioli, Natália; Sasse, Otto Rodolfo (Planta Medica, 2024)
Depression is a highly prevalent neuropsychiatric disorder worldwide. One currently accepted hypothesis of this pathogenesis is the hypothalamic–pituitary–adrenal axis dysfunction, which involves oxidative stress and brain damage. Therefore, antioxidants, such as phenolic compounds, could be used in depression. In this study, we investigated the antidepressant-like and antioxidant effects of an aqueous extract of the leaves of three species of the genus Psidium, Myrtaceae family, in mice. The exotic Psidium guajava L. and the natives Psidium guineense Sw. and Psidium cattleianum Sabine (10, 1, and 0.1 mg/kg, respectively) and fluoxetine (10 mg/kg) were administered orally (p. o.) once daily for 21 days, with or without corticosterone (20 mg/kg). After behavioral assessments (tail suspension, splash, and open-field tests), the hippocampus, prefrontal cortex, liver, kidneys, and plasma were examined to determine the oxidative stress status. The three extracts and fluoxetine treatment decreased the immobility time and counteracted the oxidative stress induced by corticosterone administration. The phenolic compounds identified as major components of the extracts, quercetin in P. guajava and P. guineense and o-coumaric acid in P. cattleianum, may be involved in the biological activities. Therefore, the aqueous leaf extracts of P. guajava, P. cattleianum, and P. guineense could be potential antidepressants helpful in treating depression and other diseases with elevated nitro-oxidative stress.
Keywords: antidepressant; corticosterone; Psidium cattleianum; Psidium guajava; Psidium guineense; Myrtaceae